Eksplorasi Sikap Pembaca terhadap Wacana Kebijakan Program Pendidikan Kejuruan Empat Tahun - Andina, Elga (Jurnal Aspirasi, 2020)
The government plans to change the length of education for several vocational high schools (SMK) to four years to prepare fully equipped graduates with operational techniques. The purpose of this study is to explore the readers’ attitudes towards the discourse on the policy of a four-year vocational education program. This research uses secondary data collected from readers' comments on published discourses on electronic media from June 11 to June 15, 2020, completed with interviews with the local government offices, SMK, and Special Region of Yogyakarta’s Chamber of Commerce (KADIN). The content analysis techniques applied to the data resulted in the four-year education program’s discourses challenged three main things: employment, financing, and the impact on the age of graduates. These three issues can be managed if the development of SMK is appropriate and in line with the needs of business and industry (DUDI). However, the link and match process between SMK and DUDI is still not optimal due to the provincial government’s lack of role as the holder of vocational education authority in the region. Strengthening responsibility and concrete work, especially from the provincial education office, is the key to vocational education development. Without improving government performance, the goal of improving the quality of education by adding one year is futile. The government must be able to ensure graduate employment by requiring SMKs to form partnerships with DUDI, a guarantee of education funding until graduation, and skills that are equivalent to graduates’ age.AbstrakPemerintah merencanakan mengubah lama pendidikan beberapa SMK menjadi empat tahun dalam rangka mempersiapkan lulusan yang lebih menguasai teknik operasional secara utuh. Tujuan studi ini adalah mengeksplorasi sikap masyarakat terhadap wacana kebijakan program pendidikan kejuruan dari tiga menjadi empat tahun. Penelitian ini menggunakan data sekunderyang berasal dari komen pembaca terhadap pemberitaan wacana di media elektronik dari tanggal 11 s.d. 15 Juni 2020, dilengkapi dengan wawancara dengan pemerintah daerah, SMK, dan KADIN Provinsi Daerah Istimewa Yogyakarta. Berdasarkan analisis konten atas data tersebut ditemukan wacana program pendidikan empat tahun menggugat tiga hal pokok: kebekerjaan, pembiayaan, dan dampaknya terhadap usia lulusan. Ketiga isu tersebut dapat ditata jika pengembangan SMK sesuai dan sejalan dengan kebutuhan dunia usaha dan/atau dunia industri (DUDI). Namun, proses link and match SMK dengan DUDI masih belum optimal, karena kurangnya peran pemerintah provinsi sebagai pemegang kewenangan pendidikan kejuruan di daerah. Penguatan tanggung jawab dan kerja konkret terutama dari dinas pendidikan provinsi merupakan kunci pengembangan pendidikan kejuruan karena tanpa perbaikan kinerja pemerintah maka tujuan peningkatan kualitas pendidikan dengan menambah satu tahun menjadi sia-sia. Pemerintah harus mampu memastikan kebekerjaan lulusan dengan mensyaratkan SMK untuk menjalin kemitraan dengan DUDI, jaminan pembiayaan pendidikan hingga lulus, dan keterampilan yang sepadan dengan usia lulusan.